The secret world of Hildegard - Winter, Jonah, 1962- (A. A. Levine, 2007)
An introduction to the life of Hildegard of Bingen, who lived in a time when women were expected only to obey--not to have visions or speak about them. Yet she did speak, and through her courage became one of the greatest mystics and composers of the medieval age.